Assessing Blending of Non‐Newtonian Fluids in Static Mixers by Planar Laser‐Induced Fluorescence and Electrical Resistance Tomography. Issue 8 (13th May 2019) - Forte, Giuseppe; Albano, Andrea; Simmons, Mark J. H.; Stitt, Hugh E.; Brunazzi, Elisabetta; Alberini, Federico
Abstract: Planar laser‐induced fluorescence (PLIF) and electrical resistance tomography (ERT) were applied simultaneously to monitor the mixing performance of a KM static mixer for the blending of non‐Newtonian fluids of dissimilar rheologies in the laminar regime. The areal distribution method was used to obtain quantitative information from the ERT tomograms and the PLIF images. Comparison of the ERT and PLIF results demonstrates the ability of ERT to detect the mixing performance in cases of poor mixing within the resolution of the measurement, though the accuracy decreases as the condition of perfect mixing is approached. Thus, ERT has the potential to detect poor mixing within the confines of its resolution limit and the required conductivity contrast, providing potential rapid at‐line measurement for industrial practitioners. Abstract : Electrical resistance tomography was selected to assess the mixing performance for blending of non‐Newtonian fluids in a static mixer. The areal fraction method allowed for comparing such measurements with planar laser‐induced fluorescence, which served as a validation technique. Advantages and limitations of the proposed technique for in‐line applications are described and evaluated.